2018
DOI: 10.1080/0284186x.2018.1445287
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell infiltration in head and neck squamous cell carcinoma and patient outcome: a retrospective study

Abstract: Oropharynx cancer with significant p16 expression showed an increased overall survival and elevated T- and B-lymphocyte infiltration, which suggests a prognostic relevance of immune cell infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
(41 reference statements)
2
49
0
1
Order By: Relevance
“…T-cell infiltration was associated with a better prognosis in all three of the tumors we examined. This was consistent with prior reports in melanoma and HNSCC 19,60 , but to our knowledge this is a novel finding in GBM that was likely missed by previous studies because T-cells are so rare in GBM.…”
Section: Discussionsupporting
confidence: 93%
“…T-cell infiltration was associated with a better prognosis in all three of the tumors we examined. This was consistent with prior reports in melanoma and HNSCC 19,60 , but to our knowledge this is a novel finding in GBM that was likely missed by previous studies because T-cells are so rare in GBM.…”
Section: Discussionsupporting
confidence: 93%
“…HNSCC generally show a stronger infiltration of immunocompetent cells than most other malignancies, including both various T cell subsets, NK cells, and monocytes [ 94 , 95 , 96 ]. However, the degree of T cell infiltration seems to vary between patients, but for most patients, the infiltrating T cells seem to include a majority of T cells with an effector memory phenotype; the fraction of naïve T cells seems to be decreased, whereas the fractions of various regulatory T cells seems to be increased [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, strong infiltration of CD3 + T cells has been associated with prolonged survival in several studies; this favorable prognostic impact seems to be mediated especially by CD8 + T cells, but a low frequency of regulatory T cell infiltration may also contribute. A recent study suggested that CD4 + T cells may also contribute to the more favorable prognosis [ 94 , 97 , 98 ]. Second, high infiltration of NK cells has also been associated with a favorable prognosis [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EGFR expression is also a prognostic biomarker but not predictive for the efficacy of cetuximab ( 22 ). Many now believe that the antitumoral activity of cetuximab is mainly an immunologic response on the non-human part of the antibody by potentiating the cytotoxic T-cell antitumor immune response, rather than through EGFR-inhibition ( 23 , 24 ). This could explain why trials with fully human EGFR-inhibitors, like panitumumab, have failed to demonstrate any survival benefit compared to or in addition to platinum-based chemotherapy ( 25 ,– 28 ).…”
Section: Changes In Primary (Chemo)radiotherapymentioning
confidence: 99%
“…This could explain why trials with fully human EGFR-inhibitors, like panitumumab, have failed to demonstrate any survival benefit compared to or in addition to platinum-based chemotherapy ( 25 ,– 28 ). HPV+ OPC could potentially benefit more of the enhanced immune response by cetuximab than HPV– OPC since HPV+ OPC contains elevated T- and B-lymphocyte infiltration and expresses viral proteins ( 24 ). To conclude, despite considerable research devoted to this topic, many questions with respect to the use of EGFR-inhibitors and in particular of cetuximab remain unanswered until now.…”
Section: Changes In Primary (Chemo)radiotherapymentioning
confidence: 99%